Grenada : Use of Fund Resources-Request for Emergency Assistance. (IMF Staff Country Reports; Country Report ;, 2004)
This paper highlights Grenada's Request for Emergency Assistance. The near-term economic outlook of Grenada is very difficult. Having grown by nearly 4 percent in the first half of the year, the economy is now projected to contract by more than 3 percent in 2004. The authorities, with the support of the international community, are responding swiftly to the emerging needs of the economy. The authorities have also requested a purchase under the IMF's policy on emergency assistance for natural disasters for an amount equivalent to SDR 2.93 million.